Pembuatan resin phenol formaldehyde sebagai prekursor untuk preparasi karbon berpori: pengaruh jenis turunan phenol terhadap karakteristik resin dan karbon - Nuryati Nuryati; Imam Prasetyo (Jurnal Rekayasa Proses, 2011)
Phenolic resin is the product of polycondensation between phenol (P) with formaldehyde (F). This research aims to study synthesis of phenol formaldehyde resin modified by adding the reactant in the form of phenol derivatives, such as tertiary butyl phenol (T), resorcinol (R) and hydroquinone (H). The product is applied as precursor for making porous carbon. Reaction of phenol formaldehyde was carried out in a stirred reactor at temperature of 90oC for 1 to 3 hours. KOH was used as catalyst. Para Toluene Sulfonic Acid (pTSA) was added to the resin as a cross linking catalyst. Carbonization process was carried out by pyrolysis at the temperature of 800oC for 1 hour. The results showed that PF and PFT resins had high density of 1.18g/cm3 . PF resin had the hardness value of 17.2 g/mm2 . The iodine number of the PF and PFT carbon was 862.3 mg/g and 794.16 mg/g, respectively. The surface area of the PF and PFT carbons were 836.7m2 /g and 702.7m2 /g, respectively.